1994
DOI: 10.1007/bf02950796
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function and deiodinase activities in rats with marginal iodine deficiency

Abstract: The hypothesis tested was whether marginal iodine deficiency for a period of 6 wk affects iodothyronine deiodinase activities in liver and brain of rats. Male rats were fed purified diets either defident or sufficient in iodine; the diets were fed on a restricted basis (60% of ad libitum intake). Body weight gain of the two groups was comparable, Iodine deficiency was evidenced by increased thyroid weight (26%), reduced urinary iodine excretion (80%), and reduced plasma T4 concentrations (22%). Activities of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
1
9
0
2
Order By: Relevance
“…The determination of type I deiodinase (ID-I) activity in liver homogenates was performed by the method described by Janssen et al (25).…”
Section: Analytical Determinationsmentioning
confidence: 99%
“…The determination of type I deiodinase (ID-I) activity in liver homogenates was performed by the method described by Janssen et al (25).…”
Section: Analytical Determinationsmentioning
confidence: 99%
“…Janssen et al (24) found no effect of iodine deficiency on hepatic ID-I activity, even though T 4 in their animals was lower. In the brain an increase in ID-II was found in iodine-deficient rats (24).…”
Section: Discussionmentioning
confidence: 74%
“…In the brain an increase in ID-II was found in iodine-deficient rats (24). In our study MID induced an PCR, plasma clearance rate; PR, production rate; V, plasma equivalent distribution volume; Q, pool quantity; TRpf, TRfp, TRps, and TRsp, rates of transport between plasma and the fast and slow pools respectively, in each direction; DRfo and DRso, disposal rate from fast and slow pool respectively; p, plasma; 2, fast pool; 3, slow pool.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The HuNa group showed significantly higher concentration of triiodothyronine (2.00 vs. 1.41 nmol/l; P < 0.05) and nonsignificantly lower thyroxine and iodine concentrations in blood serum (Figure 1). This decrease in blood serum concentrations of T 4 and iodine accompanied by an increase in T 3 concentration is indicative of an insufficient supply of iodine to the thyroid gland (Janssen, 1994) which then prefers the synthesis of the less iodine-demandingT 3 at the expense of T 4 . This findings indicates possible anti-thyroid activity of HuNa and supports the data of Huang et al (1994) who demonstrated a significant increase in T 3 and a decrease in T 4 concentrations in blood serum of rats fed a low-iodine diet containing humine substances.…”
Section: Resultsmentioning
confidence: 99%